Assessments of quaternary ammonium compounds (QAC) for in-water treatment of mussel fouling in vessel internals and sea chests using an experimental seawater pipework system. Issue 1 (2nd January 2017) - Piola, Richard; Grandison, Clare
Abstract: The primary in-water emergency treatment method for mussel fouling of internal seawater systems of Royal Australian Navy vessels is to flush with a 1% detergent solution containing quaternary ammonium compounds (QAC). Parameters for application of this treatment are based on previous research; however, much of the research has been conducted at small-scales under controlled laboratory conditions. This study examined the efficacy of QAC solutions for treating mussel biofouling under realistic field conditions using experimental seawater piping systems. The efficacy of QAC solutions was highly dependent on the size of mussels present. Chemical treatments comprising 1, 2 and 5% v v –1 QAC solution were effective at killing large (50–92 mm) mussels in the pipework and sea chest of the system following 24 h exposure. In contrast, small mussels (10–30 mm) appeared resilient to the majority of treatment regimes. Differences in water temperature, DO and pH during dosing had no discernible impact on treatment efficacy.